Desain Media Pop-Up Book Berbasis Literasi Sains Melalui Flipped Classroom Materi Ragam Bentang Alam Indonesia untuk Meningkatkan Visual Spasial Siswa Kelas III - Anggi Astriana Rijeqiani; Cindy Alfi; Mohamad Fatih (Journal of Practice Learning and Educational Development, 2025)
This study aims to develop a pop-up book design based on science literacy through a flipped classroom on the material of the diversity of Indonesia's natural appearance to improve the spatial visual of grade III elementary school students. This research uses a research and development (R&D) methodology, with a 4D model that has 4 stages, namely defining, designing, developing, and disseminating. Data collection techniques used observation, interviews, tests, and documentation. The subjects of this study were third grade students totaling 28 students. The results of media validity by media experts reached 92.5%, material experts 82.5%, and linguists 85%, all of which were categorized as very valid. In addition, the teacher's response to feasibility reached 97.5% which was categorized as very feasible. Findings based on the implementation of the pre-test and post-test with the pre-test results reaching a value of 54.8% in the “good” category and the post-test results reaching a value of 85.5% in the “very good” category. Then the pre-test and post-test results were processed using the gain normality test with a score of 0.7027 in the “high” category. Based on these findings, it can be interpreted that the development of pop-up book media based on science literacy through flipped classroom can improve the spatial visual of third grade elementary school students.